Evolução molecular das luciferases das lanternas da fase adulta e larval de elaterídeos luminescentes e filogenia molecular de Elateroidea - Amaral, Danilo Trabuco do (Universidade Federal de São Carlos, 2014)
The origin and evolution of Elateridae bioluminescence is uncertain, especially the evolution of the luciferases of different phases and lanterns of Elateridae, the relationship between structure and bioluminescence spectra and the phylogeny of neotropical species. In this study, the cDNA containing the genes of Fulgeochlisus bruchi and Pyrophorus angustus luciferases, which presente different kinetic characteristics, such as high pH optimum and a high affinity for ATP and Luciferin, were cloned. Analyses of Elateridae luciferases suggest that, regardless of the stage of life or organ (dorsal or ventral lanterns), these luciferases displayed a higher identity degree to the luciferases that present closer bioluminescence spectra, probably, due to intergenetic recombination effects. The luciferase primary sequences alignments and site-directed mutagenesis studies suggested important residues to modulate color in Elateridae, such as S247. Our phylogenetic analyzes indicated a closer relationship between Elateridae and Phengodidae, however there are diverngence between the markers used. The sequencing of mitochondrial genomes showed that the Phengodidae genomes displayed several rearrangements and gene duplication, indicating the need for further studies on this family. Our data also suggest that bioluminescence arised at least three times independently in Elateoridea from ancestors similar enzymes.
Keywords: Filogenia; Bioluminescência; Evolução; Elateridae; Ontogenia; CIENCIAS BIOLOGICAS::GENETICA